2011
DOI: 10.1007/s11224-011-9837-5
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation on the structural and electronic properties of complexes formed by thymine and 2′-deoxythymidine with different anions

Abstract: Hydrogen bonding interactions between thymine nucleobase and 2 0 -deoxythymidine nucleoside (dT) with some biological anions such as F -(fluoride), Cl -(chloride), OH -(hydroxide), and NO 3 -(nitrate) have been explored theoretically. In this study, complexes have been studied by density functional theory (B3LYP method and 6-311??G (d,p) basis set). The relevant geometries, energies, and characteristics of hydrogen bonds (H-bonds) have been systematically investigated. There is a correlation between interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Along with the studies of conventional H-bonds formed between nucleobase pairs, interest in interactions of DNA with anions has recently arisen. [44][45][46] Based on an extensive survey of the Nucleic Acid Database (NDB), Auffinger et al 44 concluded that anions (mostly Cl − and SO 4 − ) do intrude on the first hydration shell of nucleic acids and bind to electropositive amino, imino, and hydroxyl groups. Two types of such complexes formed by H-bonding of the most stable thymine tautomer with anions have recently been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the studies of conventional H-bonds formed between nucleobase pairs, interest in interactions of DNA with anions has recently arisen. [44][45][46] Based on an extensive survey of the Nucleic Acid Database (NDB), Auffinger et al 44 concluded that anions (mostly Cl − and SO 4 − ) do intrude on the first hydration shell of nucleic acids and bind to electropositive amino, imino, and hydroxyl groups. Two types of such complexes formed by H-bonding of the most stable thymine tautomer with anions have recently been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the studies of conventional H-bonds formed between nucleobase pairs, interest in interactions of DNA with anions has recently arisen. [44][45][46] Based on an extensive survey of the Nucleic Acid Database (NDB), Auffinger et al 44 concluded that anions (mostly Cl − and SO 4…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that nucleic acids contain phosphate groups and they exist as anions (thus it is clear that they are not prone to interaction with other anions). On the other hand, there are a few interesting papers devoted to the interaction of inorganic anions with nucleobases or nucleosides . Furthermore, it has been found that organic anions may stabilize the octamer made of the G‐quadruplex .…”
Section: Methodsmentioning
confidence: 99%
“…The sign of H(r) determines whether the accumulation of charge at a given point (r) is stabilizing (H(r) < 0) or destabilizing (H(r) > 0). The energies for interaction of phosphorous atom and metal cation (E P M ) are calculated by the following equation [26][27][28][29]:…”
Section: Quantum Theory Of Atoms In Molecules (Qtaim) Analysismentioning
confidence: 99%